TRANSFORMASI BUDAYA AGROFORESTRI LOKAL DALAM MENGHADAPI KESEPAKATAN PERDAGANGAN BEBAS - Rudi Hilmanto (Jurnal Penelitian Politik, 2010)
Agriculture and plantation agroforestry pattern in the years of 70s constitute cultural transformation ofagroforestry generating negative impact ecologically economic and social until this time Choice of the socializeworld to go back to nature and the negative impact ofGreen Revolution constitute matter which overshadow thegovernmentfor cymbal Go Organic 2010 Go Organic 2010 constitute opportunity which enables to constructand strengthen local commodity to own its market in free trade and also desirable by society in the country Theobjective ofthis research namely i Depicting cultural elements ofagriculture andplantation agroforestry thatexist in local community and ii Analysing cultural transformation ofagroforestry in theface offree trade Thisresearch conducted at local community as key informant taken by purposive method The organic agroforestrysystem matter is new especiallyfor local community which have the harmony with nature The local communityhas farming culture which embrace harmony with nature however this agroforestty pattern change the effectofgreen revolution existence therefore we need to transform repeatedly the cultural elements ofour agriculturewhich are beliefsystem technology andknowledge system art and language social organizational and artistryThe agroforestty culture elements combine with nature has made Indonesiajoining a transformation movement ofgoing back to nature